REJUNG BEGADISAN - Kurniawan, Rahmad; Wimbrayardi (Universitas Negeri Padang, 2024)
The purpose of creating works of art is that the artist creates new musical compositions that originate from phenomena that occur in girl culture. Rejung Begadisan's work focuses on cultivating the phenomenon of the Serawai community into sound cultivation in bringing out the atmosphere, emotions and cultural values. Creativity in the cultivation of this work uses several stages, namely: exploration, improvisation, and composition. The preparation process is carried out by applying the preparation and cultivation of elements expressed through the creativity of musical composition. In the presentation of rejung begadisan interprets moral messages such as